Support-Free Thermally Insensitive Hollow Core Fiber Coil - Wei, Xuhao; Taranta, Austin; Shi, Bo; Ding, Meng; Feng, Zitong; Richardson, David J.; Poletti, Francesco; Slavik, Radan (Journal of lightwave technology, 2023)
Light traversing an optical fiber is subject to various local phase perturbations driven by temperature. This thermal phase sensitivity is undesirable in fiber interferometers and their applications which require that a fixed, stable phase be received after propagation. The use of hollow core fiber (HCF) has been shown to reduce this thermal phase sensitivity over solid core fibers and here we propose and demonstrate how coiling HCF to a prescribed geometry can further significantly reduce this sensitivity. Our proof-of-concept experiment shows reduction by a factor of ∼90 with respect to the uncoiled HCF, and over three orders of magnitude with respect to uncoiled solid core optical fiber. Our strategy exploits a nuance of the elastic properties of fiber coils whereby the constrained thermal expansion of the composite material (fiber + coating) can result in a coil having compressed inner layers and expanded outer layers. Thermal expansion is the dominant effect responsible for thermal phase sensitivity in HCFs, and in this scheme the compressed inner coil layers compensate the thermal expansion of the outer layers. In this study we design the coil parameters using finite element simulations, studying the relationship between coil performance and its key parameters. The proof-of-principle coil has 160 mm diameter and incorporates a 548 m length of HCF out of which a 230 m section shows almost zero (slightly negative) thermal phase sensitivity. Though the coil shows low thermal phase sensitivity over tens of hours, the long-time constant viscoelastic properties of the coating materials used in the HCF under study are shown to limit these benefits. To make this strategy practical for systems with fast temperature dynamics, a coating having more stable mechanical properties could be used. For precision timing systems in which long thermal time constants are already the norm, this scheme represents a low-cost and provides a significant reduction to thermal sensitivity which is immediately practicable.